Peningkatan Keterampilan Souvenir Membuat Gantungan Kunci Pada Anak Disabilitas Grahita Ringan Kelas X Melalui Media Video Tutorial (Classroom Action Research di SLBN 1 Painan - Akila, Novia Ardana; Zulmiyetri, Zulmiyetri (Indo-MathEdu Intellectuals Journal, 2025)
This study aims to determine the improvement of keychain souvenir skills in lightly handicapped children through video tutorial media. This research uses the type of Classroom Action Research (PTK) and is carried out in the odd semester of the 2024/2025 school year. The subject of the study was 2 students of class X with mild disabilities at SLB Negeri 1 Painan. Data collection is carried out from the process of observation or observation, tests and documentation. The results of the study showed that the ability of students' keychain making skills increased after using the Video Tutorial media. This is evidenced by the improvement of skill ability from the condition of being given action in the first cycle obtained the score of C child 36%, 56%, 66%, H child 40%, 58%, 68%. Then it was continued with the continuation of the action in cycle 2 with the acquisition of 75% for C children, 83% for H children, 78% for H children, 88%. The data showed an increase in the ability to make keychains in children with mild disabilities through video tutorials.